A mixed methods systematic review of digital interventions to support the psychological health and well-being of people living with dermatological conditions - Hewitt, Rachael M.; Ploszajski, Matthew; Purcell, Catherine; Pattinson, Rachael; Jones, Bethan; Wren, Georgina H.; Hughes, Olivia; Ridd, Matthew J.; Thompson, Andrew R.; Bundy, Chris (Frontiers in Medicine, 2022)
Background Dermatological conditions can have a substantial impact on psychological as well as physical health yet dedicated face-to-face psychological support for patients is lacking. Thus, individuals may require additional support to self-manage dermatological conditions effectively. Digital technology can contribute to long-term condition management, but knowledge of the effectiveness of digital interventions addressing psychological (cognitive, emotional, and behavioural) aspects of dermatological conditions is limited. Objectives To identify, determine the effectiveness, and explore people’s views and experiences of digital interventions supporting the psychological health of people with dermatological conditions. Methods A mixed methods systematic review informed by JBI methodology. The protocol was registered on PROSPERO. Eight electronic databases were searched for papers written between January 2002 and October 2021. Data screening and extraction were conducted in Covidence. The methodological quality of studies were scrutinised against JBI critical appraisal tools. Intervention characteristics were captured using the Template for Intervention Description and Replication checklist and guide. Data were synthesised using a convergent segregated approach. The results were reported in a narrative summary. Results Twenty-three papers were identified from 4,883 references, including 15 randomised controlled trials. Nineteen interventions were condition-specific, 13 were delivered online, 16 involved an educational component, and 7 endorsed established, evidence-based therapeutic approaches. Improvements in knowledge, mood, quality of life, the therapeutic relationship, and reduced disease severity in the short to medium term, were reported, although there was substantial heterogeneity within the literature. Thirteen studies captured feedback from users, who considered various digital interventions as convenient and helpful for improving knowledge, emotion regulation, and personal control, but technical and individual barriers to use were reported. Use of established qualitative methodologies was limited and, in some cases, poorly reported. Conclusion Some web-based digital psychological interventions seem to be acceptable to people living with mainly psoriasis and eczema. Whilst some digital interventions benefitted cognitive and emotional factors, heterogeneity and inconsistencies in the literature meant definitive statements about their effectiveness could not be drawn. Interdisciplinary and patient-centred approaches to research are needed to develop and test quality digital interventions supporting the psychological health of adults living with common and rare dermatological conditions. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=285435], identifier [CRD42021285435].